Conflict and crime in municipal solid waste management: evidence from Mombasa and Nairobi, Kenya. Issue 1 (2nd January 2022) - Muindi, Kanyiva; Mberu, Blessing; Aboderin, Isabella; Amugsi, Dickson
ABSTRACT: Among the barriers to proper solid waste management (SWM), and which have received little research attention is the role of conflict and crime in the sector. This paper explores conflict and crime in SWM in Kenya's two major cities of Mombasa and Nairobi. Building on published and grey literature on crime and conflict in the sector, we present findings from a household survey and qualitative discussions with key stakeholders in SWM. The findings indicate that the pulling out of municipal authorities from the provision of SWM services, coupled with the 'informalization' of the Kenyan economy in the 1990s and the increase in both unemployment and poverty set the stage for the involvement of criminal elements in the sector. Crimes in the sector include corrupt practices such as well-connected individuals getting awarded service provision contracts that they do not honour, illegal activities on the dumpsites where gangs control access by transporters, and recovery of recyclables. In addition, there is violence from waste pickers towards outsiders thought to encroach on their territory. There is a need for county authorities to take over the control of waste management to address the huge public health implications it poses to the city.